Photographic Transgressions in Carol Shields’s “Scenes” - Szatanik, Zuzanna (Romanica Silesiana)
<!--EndFragmen-->The general aim of this article is to discuss ways in which an acclaimed Canadian writer, Carol Shields, employs, and simultaneously subverts, photographic metaphors in her short story titled “Scenes.” Shields skillfully arranges a series of scenes from Frances’s — the protagonist’s — past into a concise biography. Owing to their affinity to photographs, the scenes from Frances’s life might be attributed the status of objective and honest representations of reality which function as truthful evidence of what happened. Importantly, however, while Shields’s story evokes the photographic associations, it simultaneously calls in question their documentary reliability. In other words, Frances’s fragmentary biography — shown in (verbally constructed) images or flashes — undermines the concepts of both, a photograph as a documentary inscription of the truth, and language as a fitting medium of describing this truth. Key words: Photography, representation, biography, language.